Brain evolution by design : from neural origin to cognitive architecture - Shigeno, Shuichi; Murakami, Yasunori; Nomura, Tadashi (Springer, 2017)
This book presents a new, detailed examination that explains how elegant brains have been shaped in evolution. It consists of 19 chapters written by academic professionals in neuroscience, opening with the origin of single-celled creatures and then introducing primordial types in invertebrates with the great abundance of the brains of vertebrates. Important topics are provided in a timely manner, because novel techniques emerged rapidly as seen, for examples, in the next-generation sequencers and omics approaches. With the explosion of big data, neural-related genes and molecules is now on the radar. In fact, Europe´s big science and technology projects, a 1 billion plan called the Human Brain Project and the Blue Brain Project to understand mammalian brain networks, have been launched in recent years. Furthermore, with the rise of recently advanced artificial intelligence, there is great enthusiasm for understanding the evolution of neural networks. The views from brain evolution in nature provide an essential opportunity to generate ideas for novel neuron- and brain-inspired computation. The ambition behind this book is that it will stimulate young scientists who seek a deeper understanding in order to find the basic principles shaping brains that provided higher cognitive functions in the course of evolution.
Keywords: Brain -- Evolution.; elektronické knihy; electronic books